2022
DOI: 10.1186/s13229-022-00514-5
|View full text |Cite
|
Sign up to set email alerts
|

Early life sleep disruption potentiates lasting sex-specific changes in behavior in genetically vulnerable Shank3 heterozygous autism model mice

Abstract: Background Patients with autism spectrum disorder (ASD) experience high rates of sleep disruption beginning early in life; however, the developmental consequences of this disruption are not understood. We examined sleep behavior and the consequences of sleep disruption in developing mice bearing C-terminal truncation mutation in the high-confidence ASD risk gene SHANK3 (Shank3ΔC). We hypothesized that sleep disruption may be an early sign of developmental divergence, and that clinically relevan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 61 publications
(165 reference statements)
5
19
0
Order By: Relevance
“…Single housed mice generate ~6500 bouts of rest and PA per day, this is in agreement with data for C57BL/6 obtained by a HCM system using force plates [44]. Eighty percent are bouts of PA corresponding to only ~20% of the file time (see also [45,46] later confirmed and extended by correlative assessment of home-cage periods of long rest using piezo-electric sensor [48], IR-sensor [20,49], CCD [21,22], and electric-field sensor [50] based HCM techniques combined with EEG-EMG recordings. The results of these studies show a correlation >0.9 between NREM and REM sleep, on the hand, and the animals being still ≥40s, on the other.…”
Section: Bouts Of Rest and Pasupporting
confidence: 86%
See 2 more Smart Citations
“…Single housed mice generate ~6500 bouts of rest and PA per day, this is in agreement with data for C57BL/6 obtained by a HCM system using force plates [44]. Eighty percent are bouts of PA corresponding to only ~20% of the file time (see also [45,46] later confirmed and extended by correlative assessment of home-cage periods of long rest using piezo-electric sensor [48], IR-sensor [20,49], CCD [21,22], and electric-field sensor [50] based HCM techniques combined with EEG-EMG recordings. The results of these studies show a correlation >0.9 between NREM and REM sleep, on the hand, and the animals being still ≥40s, on the other.…”
Section: Bouts Of Rest and Pasupporting
confidence: 86%
“…Pack et al [47] found by comparing EEG and EMG recording with CCD a >90% agreement between long periods of rest (CCD; ≥30s) and EEG-EMG pattern of NREM and REM sleep. These observations were later confirmed and extended by correlative assessment of home-cage periods of long rest using piezo-electric sensor[48], IR-sensor[20, 49], CCD[21, 22], and electric-field sensor [50] based HCM techniques combined with EEG-EMG recordings. The results of these studies show a correlation >0.9 between NREM and REM sleep, on the hand, and the animals being still ≥40s, on the other.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, sleep loss in mice during the visual CP impairs cortical plasticity necessary for normal development of binocular vision (Renouard et al, 2022, this issue;Zhou et al, 2020). Consistent with CPs in complex behavior, sleep disruption in early life leads to persistent alterations in social interactions and cognition in wild type rodents (voles) and in an autism mouse model (Jones et al, 2021(Jones et al, , 2019Lord et al, 2022;Milman et al, 2023). Collectively, these findings may explain why during the 3 rd -4 th postnatal week (when many CPs occur in rodents) SD impacts PFC gene expression in ways not found at other ages.…”
Section: Sd Induced Changes Unique To P24: a Window Of Vulnerability?mentioning
confidence: 99%
“…The Shank3 mouse model is the only one in which sleep, and the impact of sleep loss has been examined early in life and in adults. Shank3 ΔC−/- have been shown to develop an abnormal response to sleep loss during the early developmental period ( Medina et al, 2022 ), while early-life sleep disruption in Shank3 ΔC−/+ has been shown to affect behavior in adulthood ( Lord et al, 2022 ). Mutations in Shank3 have also been shown to lead to deficits in homeostatic plasticity during the critical period, although those studies were done in a different mutant line ( Shank3B ) from the sleep studies ( Tatavarty et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%